Hong-Ou-Mandel Dip Measurements of Two Independent Weak Coherent Pulses for Free Space Quantum Key Distribution Systems - Tawfeeq, Shelan Khasro; Khaleel, Ahmed Ismael (Iraqi Journal of Laser, 2021)
Preparation of identical independent photons is the core of many quantum applications such as entanglement swapping and entangling process. In this work, Hong-Ou-Mandel experiment was performed to evaluate the degree of indistinguishability between independent photons generated from two independent weak coherent sources working at 640 nm. The visibility was 46%, close to the theoretical limit of 50%. The implemented setup can be adopted in quantum key distribution experiments carried out with free space as the channel link, as all the devices and components used are operative in the visible range of the electromagnetic spectrum.